Medical Science in the Safavid Period (16-17th Centuries) - Fataliyev, Vahab (Scholarya Demo Journal of Ruby, 2020)
The article deals with Safavid period medical science and practice described by European travelers who visited the territory of the Safavid Empire in the 17th century. Along with traveler’s records, the author used several articles and books for analysis. The article provides information about the development of the medical science and practice, many natural things used as a medicine in that period. Based on the studied materials, it is possible to see the high level of development of medical science in the territory of the Safavids. Thanks to the numerous works written by Safavid physicians during this period, the medicines we encountered in these works, methods of their preparation and their effective use in the treatment of diseases considered deadly at that time, we can acquire thorough knowledge about the medical science of that period. Moreover, considering the notes of travelers who visited the Safavid state for various purposes, we can further develop our knowledge of the medical science of that period. Travelers provide us with a lot of detailed information, show their admiration for Safavid medical science as well as their critical views. Thanks to the travelogues, we learn that various water sources were used in the Safavid state as a means of treatment, the pharmaceutical products made here were of high quality and even transported to Europe. It also reveals that Safavid physicians still learned anatomy from Galien and Ibn Sina as there was no new research in this field, and surgery was not well developed. We also get information about the most common diseases during this period, based on both local and foreign sources. Adam Oleari even mentioned prevalent diseases according to regions.